Fully Differential Cross Sections for Photo-Double-Ionization of D2_ - Weber, Th.; Czasch, A.; Jagutzki, O.; Müller, A.; Mergel, V.; Kheifets, A.; Feagin, J.; Rotenberg, E.; Meigs, G.; Prior, M. H.; Daveau, S.; Landers, A. L.; et al. (My University, 2004)
We report the first kinematically complete study of the four-body fragmentation of the D2 molecule following absorption of a single photon. For equal energy sharing of the two electrons and a photon energy of 75.5 eV, we observed the relaxation of one of the selection rules valid for He photo-double-ionization and a strong dependence of the electron angular distribution on the orientation of the molecular axis. This effect is reproduced by a model in which a pair of photoionization amplitudes is introduced for the light polarization parallel and perpendicular to the molecular axis.